International competition and firm performance: Evidence from Belgium - Jan De Loecker; Catherine Fuss; Johannes Van Biesebroeck (National Bank of Belgium, 2014)
We evaluate the impact of international competition on firm-level perfor- mance in Belgium. In the manufacturing sector we consider both the impact of global competition through measures of import penetration and the impact of within-EU competitiveness using measures of relative labor cost. In selected manufacturing sectors we identify the strength of international competition through a firm's proximity to the border. In both instances, we consider the impact on a variety of performance dimensions to learn about the mechanisms and about firms' adjustment to these competitive pressures
Keywords: 330; Efficiency; Markup; Competition; Import penetration; Internationaler Wettbewerb; Unternehmenserfolg; Industrie; Arbeitskosten; Import; Belgien